Laser Writing of Janus Graphene/Kevlar Textile for Intelligent Protective Clothing - Wang, Huimin; Wang, Haomin; Wang, Yiliang; Su, Xinyi; Wang, Chunya; Zhang, Mingchao; Jian, Muqiang; Xia, Kailun; Liang, Xiaoping; Lu, Haojie; Li, Shuo; Zhang, Yingying (ACS nano, 2020)
Protective clothing plays a vital role in safety and security. Traditional protective clothing can protect the human body from physical injury. It is highly desirable to integrate modern wearable electronics into a traditional protection suit to endow it with versatile smart functions. However, it is still challenging to integrate electronics into clothing through a practical approach while keeping the intrinsic flexibility and breathability of textiles. In this work, we realized the direct writing of laser-induced graphene (LIG) on a Kevlar textile in air and demonstrated the applications of the as-prepared Janus graphene/Kevlar textile in intelligent protective clothing. The CO and N–C bonds in Kevlar were broken, and the remaining carbon atoms were reorganized into graphene, which can be ascribed to a photothermal effect induced by the laser irradiation. Proof-of-concept devices based on the prepared graphene/Kevlar textile, including flexible Zn–air batteries, electrocardiogram electrodes, and NO2 sensors, were demonstrated. Further, we fabricated self-powered and intelligent protective clothing based on the graphene/Kevlar textile. The laser-induced direct writing of graphene from commercial textiles in air conditions provides a versatile and rapid route for the fabrication of textile electronics.